The Eco‐Exposome Concept: Supporting an Integrated Assessment of Mixtures of Environmental Chemicals. (29th December 2021) - Scholz, Stefan; Nichols, John W.; Escher, Beate I.; Ankley, Gerald T.; Altenburger, Rolf; Blackwell, Brett; Brack, Werner; Burkhard, Lawrence; Collette, Timothy W.; Doering, Jon A.; Ekman, Drew; Fay, Kellie; et al.
Abstract: Organisms are exposed to ever‐changing complex mixtures of chemicals over the course of their lifetime. The need to more comprehensively describe this exposure and relate it to adverse health effects has led to formulation of the exposome concept in human toxicology. Whether this concept has utility in the context of environmental hazard and risk assessment has not been discussed in detail. In this Critical Perspective, we propose—by analogy to the human exposome—to define the eco‐exposome as the totality of the internal exposure (anthropogenic and natural chemicals, their biotransformation products or adducts, and endogenous signaling molecules that may be sensitive to an anthropogenic chemical exposure) over the lifetime of an ecologically relevant organism. We describe how targeted and nontargeted chemical analyses and bioassays can be employed to characterize this exposure and discuss how the adverse outcome pathway concept could be used to link this exposure to adverse effects. Available methods, their limitations, and/or requirement for improvements for practical application of the eco‐exposome concept are discussed. Even though analysis of the eco‐exposome can be resource‐intensive and challenging, new approaches and technologies make this assessment increasingly feasible. Furthermore, an improved understanding of mechanistic relationships between external chemical exposure(s), internal chemical exposure(s), and biological effects could result in the development of proxies, that is, relatively simple chemical and biological measurements that could be used to complement internal exposure assessment or infer the internal exposure when it is difficult to measure. Environ Toxicol Chem 2022;41:30–45. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Illustration of the eco‐exposome assessment and how chemical analysis and bioassays could be used to estimate internal exposure. MIE = molecular initiation event; KE = key event; AO = adverse outcome.